Transient Free Convection Flow of an Elastico-Viscous Fluid Past an Infinite Vertical Plate - Deka, R.; Das, U.N.; Soundalgekar, V.M. (Engineering Transactions, 1995)
A solution to the problem of an unsteady, non-isothermal flow of an elastico-viscous fluid in a half-space is presented. The flow is induced by a temperature jump on the limiting plane. The constitutive equations of Walters' liquid B' are used.